Delayed-Interval Delivery in Dichorionic Twin Pregnancies: A Case Report of 154 Latency Days - Soares de Frias, C (2020)
Premature delivery often complicates multifetal pregnancies, placing neonates at risk of serious morbidity and mortality. In select cases, preterm birth of one sibling may not require delivery of the remaining fetus(es), which may remain in utero for a delayed-interval delivery, consequently improving neonatal morbidity and mortality. Currently, there is no consensus on the best protocol for the optimal management of these cases. We report one case of delayed-interval delivery of a dichorionic pregnancy assisted in our center. In this case, prophylactic cerclage, tocolytic therapy and administration of broad-spectrum prophylactic antibiotics enabled delivery at 37 weeks, corresponding to 154 days of latency, which is, to our knowledge, the longest interval described in the literature. The attempt to defer the delivery of the second fetus in peri-viability is an option that should be offered to parents after counseling, providing that the clinical criteria of eligibility are fulfilled. The correct selection of candidates, combined with the correct performance of procedures, as well as fetal and maternal monitoring and early identification of complications increase the probability of success of this type of delivery.